The Relationship between Toponymy and Linguistics - Oana- Maria Poenaru (Girigan) (Anadiss, 2013)
Through this article I tried to point out that the toponymy of a region can be differently studied, given the concerns of the one conducting the research, thus the concern for toponymy must preocupy the geographer and historian but olso the linguist which aims to discover the origin of some names on purely linguistic criteria (of phonetic, semantic, onomasiologic nature and so on). The linguistic material (exemplified toponyms) obtained from field surveys (Upper Bistriţa basin) and the study of specialised historical and geographical documents aims to capture relatively new concepts such as polarization and differentiation, presenting the meaning, etymology and changes occurring over time in the process of denomination of a reality. I also tried to capture the fact that common names and place names do not exclude each other, but are in a reciprocity relationship, despite some semantic, derivational and grammatical particularities.